Influence of performance feedback and academic performance on parent–family involvement and parent satisfaction in US schools - Venugopal Prabhakar, G.; Swapna Bhargavi, G.; Ramesh Reddy, P.; Shehab, M. (Journal of Community Psychology, 2023)
Parental and family involvement in schools has been a concern for educators and administrators. The authors set out to assess the path directions and significance of the interrelationships between Performance Feedback (PF), Academic Performance (AP) on Parent–Family Involvement (PFI), and Parent Satisfaction (PS) in schools. This study utilizes data from the PFI in Education Survey 2019 under the National Household Education Surveys program done by the US Department of Education. The sample for this research is 954 parents. Structural equation modeling was employed using AMOS. Results establish the three research propositions: influence of PFI on PS with the mediation of AP and PF, influence of AP on PS is moderated by PF, influence of AP on PFI is moderated by PF. The findings are important for school administrators and all stakeholders for ensuring greater PFI, improved PF and AP of students, and higher PS. This study is unique in assessing the interactional effects of the variables considered. The study also establishes mediating and moderating influences and offers new insights in understanding the influences on PFI and PS and some bidirectional effects. © 2023 Wiley Periodicals LLC.
Keywords: academic performance; dept.bus; parent satisfaction; parent–family involvement; peer-reviewed; performance feedback